CONTRIBUTION OF PHYSIOTHERAPY IN REDUCING THE RISK OF FALL IN THE ELDERLY - Cătălina-Mihaela Dascălu; Marius Neculăeș; Lucaci Paul (Sport şi Societate)
Nowadays, one of the major concerns of the specialists in the field of health is represented by finding optimal solutions to prevent falls among the elderly.The study was carried out on a group of 10 elderly people from a retirement home in Iasi, who were given a customized physiotherapy program, after being functionally evaluated using Tinetti walking test, Tinetti balance test and Romberg test.The research results highlight an improvement in balance and muscle control following specific physiotherapy programs.The conclusions of the current study highlight the fact that physiotherapy programs can reduce the risk of falls in the elderly by improving balance and walking abilities.